The Openness of the Baradouni Poem: A Socio-Textual Study (The International Journal of Educational Sciences and Arts, 2024)
This paper aimed at investigating the Baradouni's Diwan Rawagh Al-Masabih as a sample and the openness of the Baradouni's poem from a socio-textual perspective. The study dealt with the sociolinguistic situation and then examined the main theme and sub-themes. The researcher also examined at the level of structure of the language two dominant stylistic features, which are intonation and interrogative. At the level of rhythmic structure, the researcher also investigated some features of the rhythm of the Baradouni text that differs from the rhythm of the Khalili prosody. At the level of intertextuality, the study focused on the intertextuality of the Baradouni's poem with the literary, religious, philosophical, cultural, and cognitive textual structures. The researcher concluded by investigating the voices in the Baradouni's poem and identifying its voice.
Keywords: Socio-Textual; the Openness; Intertext; Rawagh Al-Masabih; Baradouni; Yemen